The Impact of Divestment and Acquisition on Company Performance - Depince Pigai; Hasim As'ari (PT FORMOSA CENDEKIA GLOBAL, 2026)
Most companies in Indonesia restructured their portfolios in 1997 during the economic crisis, but the results were mixed after restructuring their portfolios. After the economic crisis, portfolio restructuring in the form of divestments and acquisitions in Indonesia continues with mixed results, as well as the results of divestment research and acquisitions are still diverse and not conclusive. In developing countries, especially in Indonesia, there have not been many research results on divestment and acquisition with moderated company size. The study examined the effect of divestment, acquisition and company size as moderation variables on a company's performance. A total of 54 issuers are listed in the IDX 2011 - 2019 which conducts divestments and acquisitions. The study used multiple regression analysis and moderation regression analysis (MRA) which that explains the relationship 2 independent variables. Divestment and acquisitions on the research proven to have an impact on firm performance and firm size as a moderating variable proved to be able to moderate the impact of the divestment of the firm performance but not proven to be able to moderate the impact of acquisitions on firm performance Expected results of this research are beneficial to the development of the theory of portfolio restructuring, beneficial for executives, managers, business analysts, and investors to determine the priority of the type of restructuring the portfolio to improve the performance of the company